P0918LONGITUDINAL TRAJECTORIES OF NUTRITIONAL PARAMETERS WITH ORAL NUTRITIONAL SUPPLEMENT USE AMONG NON-DIALYSIS CHRONIC KIDNEY DISEASE PATIENTS. (6th June 2020) - Wong, Michelle; Renouf, Dani; Zheng, Sophia; Sheriff, Zainab; Levin, Adeera
Abstract: Background and Aims: Malnutrition and protein-energy wasting are complications of advanced CKD associated with increased risk of mortality and morbidity. In the province of British Columbia, Canada, a Nutritional Supplement Policy stewarded by renal dietitians guides prescription of oral nutritional supplements (ONS). To date, there have been a lack of studies assessing the effects of ONS among non-dialysis CKD patients (CKD-ND). The aim of the study was to assess longitudinal trajectories of nutrition, inflammation and associated biochemical parameters following initiation of ONS among CKD-ND patients. Method: In this retrospective cohort study of adult CKD-ND patients who initiated follow-up at multidisciplinary Kidney Care Clinics during 2013-2015, we used radar charts to examine longitudinal trajectories of nutritional, inflammation and related parameters over 2 years, among patients who had at least one ONS prescription and who had available lab data for the following 8 parameters within any given time interval: body mass index (BMI), serum albumin, bicarbonate, phosphate, parathyroid hormone, ferritin, neutrophil-to-lymphocyte ratio (NLR) and haemoglobin. Mean values of each parameter were plotted at 6-month intervals from the first prescription of ONS, up to 29 months. Results: There were 963, 692, 569, 481, 425 patients with available data during the intervals at month 0-5, 6-11, 12-17, 18-23 and 24-29 following the first ONS prescription, respectively. Mean serum albumin increased from a mean of 37 to 40 g/L over the 29-month period after ONS initiation, while mean NLR declined from 4.5 to 3.6 (Figure). Mean serum ferritin also declined slightly from 293 to 261 µg/L at 3 months and remained stable thereafter. There were small fluctuations in mean BMI (range 24.5 to 25.1 kg/m 2 ), bicarbonate (range 24 to 25 mmol/L), PTH (range 15.5 to 18.0 pmol/L). Mean haemoglobin rose from 108 g/L in the first interval to 116 g/L in the last interval. Mean serum phosphate changed minimally from 1.4 to 1.3 mmol/L. Conclusion: Among CKD-ND patients who had at least one ONS prescription, serum albumin increased, while there was a decrease in inflammation parameters (NLR and ferritin), and other variables had small fluctuations over the 2+ year follow-up. Future analyses will include multivariable-adjusted models to assess the associations of ONS treatment with nutritional variables and with clinical outcomes, including progression to end-stage kidney disease.